Neanderthal use of plants and past vegetation reconstruction at the Middle Paleolithic site of Abrigo de la Quebrada (Chelva, Valencia, Spain) - Esteban, I. (2018)
Despite phytoliths having been used to understand past human use of plants and palaeoenvironment in Middle Paleolithic sites, little is known on this aspect in the welldocumented central region of Mediterranean Iberia. This paper presents the first phytolith andmineralogical study conducted at Abrigo de la Quebrada (Chelva, Valencia). Forty-one samples were analyzed through phytoliths and Fourier transform infrared spectroscopy (FTIR) from different areas, stratigraphic levels, and archeological contexts (hearth, hearth-related, and non-hearth-related sediments) of the shelter. The results obtained point towards a different pattern of preservation in the site depending firstly on the stratigraphy and secondly on the area where the samples were collected. Postdepositional processes that may have chemically affected phytolith preservation are discussed. Grasses are the main plant component identified in all the samples while woody plants are scarce. The abundance of grasses in the non-hearth-related sediments might be related, at least partially, to the dispersion of ashes from hearths, as indicated by the FTIR results. The results are indicative of an occupation of the site during the spring-autumn season. At this time, the area would be dominated by a semi-open environment with supramediterranean vegetation.